2021
DOI: 10.1186/s10020-021-00303-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-27a-3p promotes the osteogenic differentiation by activating CRY2/ERK1/2 axis

Abstract: Background Osteoporosis seriously disturbs the life of people. Meanwhile, inhibition or weakening of osteogenic differentiation is one of the important factors in the pathogenesis of osteoporosis. It was reported that miR-27a-3p reduced the symptoms of osteoporosis. However, the mechanism by which miR-27a-3p in osteogenic differentiation remains largely unknown. Methods To induce the osteogenic differentiation in MC3T3-E1 cells, cells were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
(48 reference statements)
1
11
0
Order By: Relevance
“…In accordance with the present results, previous studies have demonstrated that miR-27a-3p enhanced osteogenic differentiation of MC3T3-E1 preosteoblasts ( Ren et al, 2021 ; Xu et al, 2018a ; Xu et al, 2018b ). However, several studies have shown that miR-27a-3p inhibits the osteogenic differentiation of MC3T3-E1 preosteoblasts or BMSCs ( Xu et al, 2020 ; Zeng et al, 2021 ; Furesi et al, 2022 ; Zhang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with the present results, previous studies have demonstrated that miR-27a-3p enhanced osteogenic differentiation of MC3T3-E1 preosteoblasts ( Ren et al, 2021 ; Xu et al, 2018a ; Xu et al, 2018b ). However, several studies have shown that miR-27a-3p inhibits the osteogenic differentiation of MC3T3-E1 preosteoblasts or BMSCs ( Xu et al, 2020 ; Zeng et al, 2021 ; Furesi et al, 2022 ; Zhang et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…For instance, miR‐27a‐3p was downregulated in both PI vs. PD and PI vs. PIC. MiR‐27a‐3p can directly target CRY2, promoting the phosphorylation of ERK1/2, inhibiting apoptosis, and promoting the osteogenic differentiation of MC3T3‐E1 cells 25 . Our previous research found that miR‐27a‐3p was downregulated in dogs with peri‐implantitis compared with healthy dogs, 17 and miR‐27a‐3p may target DKK2 and SFRP1 to promote reosseointegration in the regenerative treatment of peri‐implantitis 14 .…”
Section: Discussionmentioning
confidence: 96%
“…MiR-27a-3p can directly target CRY2, promoting the phosphorylation of ERK1/2, inhibiting apoptosis, and promoting the osteogenic differentiation of MC3T3-E1 cells. 25 Our previous research found that miR-27a-3p was downregulated in dogs with peri-implantitis compared with healthy dogs, 17 and miR-27a-3p may target DKK2 and SFRP1 to promote reosseointegration in the regenerative treatment of peri-implantitis. 14 Recent studies suggested that miR-27a-3p promotes autophagy and apoptosis in IL-1β-treated articular chondrocytes in osteoarthritis through PI3K/AKT/mTOR signaling.…”
Section: The Upregulated Genes (Targets Of Lowmentioning
confidence: 94%
“…No differentially abundant miRNA was identified based on differential expression analysis except for miR-27a-3p, which was more abundant in high-compared with low-IgG samples (P = 0.028; Figure 2C). This miR-27a-3p showed to promote osteogenic differentiation in pre-osteoblast (MC3T3-E1) cells (Ren et al, 2021), suggesting a role in the osteogenesis of neonatal calves.…”
Section: Assessment Of Microrna Profiles In Small Extracellular Vesic...mentioning
confidence: 90%